GEOGRAPHICAL DIMENSIONS TO GLOBAL OCEANS GOVERNANCE. Issue 1 (1st January 2023) - Schofield, Clive
Abstract: The global ocean dominates the world spatially. While there is growing understanding that these vast marine spaces are more valuable than ever, there is also mounting concern over escalating threats to the marine environment and vulnerable ecosystems. Governance of the oceans is both inherently and increasingly geographical in character, illustrated here through consideration of the zonal system of maritime jurisdiction, the definition of baselines along the coast, delineation of the outer limits of maritime zones and delimitation of maritime boundaries. In response to the increasing diversity and intensity of activities and uses of the ocean, a variety of geospatial management approaches are being applied. Geography and geographers will therefore have a salient role to play in present and future global oceans governance.